Myrtaceae in the Atlantic forest: their role as a ‘model’ group - Lucas, Eve J; Bünger, Mariana O (Biodiversity and conservation, 2015)
Myrtaceae is one of the richest families in the Atlantic Forest, a priority biodiversity hotspot that continues to be highly threatened, subject to rapid urbanisation and high levels of resource exploitation. Authors have suggested that individual lineages can be used as models to study biome evolution and ecology and to provide data for conservation planning in these areas. Here we review how Myrtaceae fit the ‘model’ criteria and examine the family’s distribution throughout the Brazilian Atlantic Forest answering the questions: What is the ecological representation of Myrtaceae in the Atlantic Forest?; What is the current taxonomic situation of Myrtaceae in the biome?; What is the current phylogenetic understanding in the family?; Does the historical timeframe of the lineage coincide with that of the biome?; Can Myrtaceae be used to discuss species diversity hotspots within the Atlantic forests?; What is the role of Myrtaceae in conservation strategy? And finally, Can Myrtaceae be used as a ‘model’ taxon? The concept of the ‘model taxon’ is also discussed. The review concludes that taxonomic and phlyogenetic understanding in Myrtaceae are rapidly increasing, giving hope that taxonomic stability, easy species identification and management are realistic in a way unthinkable only a few decades ago. Myrtaceae function well as a ‘model’ within the Atlantic forest but fit some criteria better than others. Taxa can qualify as ‘models’ representing different times and pressures in the history of a given biome; each tells its own story. For future ‘model’ group studies to have maximum impact and implementation for evolutionary studies and conservation strategy, synthetic studies of multiple ‘model’ groups using multiple approaches are required; only then can a predictive understanding of past and future processes in the biomes concerned, be glimpsed.